Achievements of European projects on membrane reactor for hydrogen production. (10th September 2017) - Di Marcoberardino, Gioele; Binotti, Marco; Manzolini, Giampaolo; Viviente, José Luis; Arratibel, Alba; Roses, Leonardo; Gallucci, Fausto
Abstract: Membrane reactors for hydrogen production can increase both the hydrogen production efficiency at small scale and the electric efficiency in micro-cogeneration systems when coupled with Polymeric Electrolyte Membrane fuel cells. This paper discusses the achievements of three European projects (FERRET, FluidCELL, BIONICO) which investigate the application of the membrane reactor concept to hydrogen production and micro-cogeneration systems using both natural gas and biofuels (biogas and bio-ethanol) as feedstock. The membranes, used to selectively separate hydrogen from the other reaction products (CH4, CO2, H2 O, etc.), are of asymmetric type with a thin layer of Pd alloy (<5 μm), and supported on a ceramic porous material to increase their mechanical stability. In FERRET, the flexibility of the membrane reactor under diverse natural gas quality is validated. The reactor is integrated in a micro-CHP system and achieves a net electric efficiency of about 42% (8% points higher than the reference case). In FluidCELL, the use of bio-ethanol as feedstock for micro-cogeneration Polymeric Electrolyte Membrane based system is investigated in off-grid applications and a net electric efficiency around 40% is obtained (6% higher than the reference case). Finally, BIONICO investigates the hydrogen production from biogas. While BIONICO has just started, FERRET and FluidCELL are in their third year and the two prototypes are close to be tested confirming the potentiality of membrane reactor technology at small scale. Highlights: Objectives and results of three European projects FERRET, FluidCELL, BIONICO. Membrane reactor enhance hydrogen production and micro-cogeneration system efficiency. Hydrogen production from natural gas and biofuels (biogas and bioethanol). Micro-cogeneration net electric efficiency 6–8% points higher than reference cases. Hydrogen production efficiency from biogas higher than 70%.